2008
DOI: 10.1017/s1751731108002772
|View full text |Cite
|
Sign up to set email alerts
|

Horses do not exhibit motor bias when their balance is challenged

Abstract: In many equestrian pursuits such as dressage and show-jumping, it is important that the horse exhibits the same level of balance when ridden to the left as when ridden to the right in canter -that is, to show no motor bias. It is a long-held belief within such disciplines that to reduce bias that exists in horses and thus to enhance symmetry of performance to the left and right, the horse needs to be worked equally in both directions, although there is a lack of scientific evidence of this influencing bias. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 16 publications
(28 reference statements)
1
7
0
Order By: Relevance
“…Together, these findings support the idea that social coordination is an important driving force for the evolution of population level laterality [3] and that population level motor laterality may be determined more by the nature of the tasks than their complexity [183]. Several motor laterality studies on horses have shown how humans may influence the expression of motor laterality in domestic species, for instance, through breeding and training [54,57,58,94]. For example, horses that were trained or ridden showed population level biases in locomotion and standing, while unridden and untrained horses had no population bias [54,58].…”
Section: Motor Lateralitysupporting
confidence: 68%
See 1 more Smart Citation
“…Together, these findings support the idea that social coordination is an important driving force for the evolution of population level laterality [3] and that population level motor laterality may be determined more by the nature of the tasks than their complexity [183]. Several motor laterality studies on horses have shown how humans may influence the expression of motor laterality in domestic species, for instance, through breeding and training [54,57,58,94]. For example, horses that were trained or ridden showed population level biases in locomotion and standing, while unridden and untrained horses had no population bias [54,58].…”
Section: Motor Lateralitysupporting
confidence: 68%
“…Several motor laterality studies on horses have shown how humans may influence the expression of motor laterality in domestic species, for instance, through breeding and training [54,57,58,94]. For example, horses that were trained or ridden showed population level biases in locomotion and standing, while unridden and untrained horses had no population bias [54,58]. However, other reports have suggested that training reduces laterality in locomotion [94], and since untrained horses are usually younger, age may also have played a role (see Section 4.4).…”
Section: Motor Lateralitymentioning
confidence: 99%
“…In addition, thoroughbred-racing horses showed a population bias to place the left forelimb in front of the other forelimb during grazing (McGreevy and Rogers, 2005). These two measures of limb preference appear to be independent of each other since Wells and Blache (2008) found no association between forelimb preference while grazing and limb preference while cantering. On the other hand in feral horses, Austin and Rogers (2012) showed no population preferences to place one forelimb in front of the other during grazing, stressing the hypothesis that limb preference in domestic horses may be entrained by human handling.…”
Section: Introductionmentioning
confidence: 93%
“…In line with this work, McGreevy and Thomson (2005) population bias of forelimb preference while grazing than thoroughbreds, and Quarter Horses trained for cutting, which requires equal agility on the left and right sides, show no bias for the same measure. In addition, Wells and Blache (2008) reported a right population bias for forelimb preference while grazing in older horses (that had previously been ridden), whereas that was not the case for young horses (that had never been ridden).…”
Section: Introductionmentioning
confidence: 95%
“…While the left hemisphere has been shown to be preferentially used for established learned responses, categorization of stimuli and approach behavior, the right hemisphere has been proposed as being dominant in information processing for emergency reactions, stress responses, novelty, and social interactions [29,30,31,32,33,34,35,36]. The motor laterality is assumed to be the result of brain hemispheric modulation through former experiences and training [27,37]. Sensory laterality may be independent of previous experiences and may change more flexible between left and right organ use with different tasks than reported for motor laterality [31,38].…”
Section: Introductionmentioning
confidence: 99%